HAK MENDAHULUI PENERIMAAN NEGARA BUKAN PAJAK DALAM MEMPEROLEH PELUNASAN UTANG DALAM PENUNDAAN KEWAJIBAN PEMBAYARAN HUTANG PT. INTERNUX - Sulistiyono Catur Kurnia Putra (2021)
The purpose of this research is to study the settlement of Credit Preference Creditors of the Ministry of communication and Information Technology (Menkominfo) as the regulator of Radio Frequency Usage Rights Fee (BHP) owed by PT. Internux. The research scope is suspension of Payment (PKPU). In the case of PT. Internux which is in arrears for radio frequency BHP payments as Non-Tax State Revenue (PNBP), Menkominfo ratified the homologation on the results of the suspension of Payment (PKPU) to PT. Internux by the Central Jakarta Commercial Court. The findings of this research are that Menkominfo do not want to submit to the homologation that was passed and continue to revoke PT. Internux is based on debt that has not been paid for 2 years. Research is a juridical normative with data collection in the form of regulations related to telecommunications, bankruptcy and PKPU, books, journals and official websites. The conclusion of this research is that in PKPU practice, Menkominfo is often positioned as a concurrent creditor. His position should be as Preperence Creditors because PNBP claims belonging to the Minister of Communication and Informatics are invoices that are Preference in nature and must be prioritized in payment. Thus, when there is debt restructuring in PKPU reconciliation, the receivables owned by the State have their position as Preferred Creditor